PRODUCTION OPTIMIZATION AND FOOD NEEDS PROVISION DISTRIBUTION IN SOUTH HALMAHERA REGENCY, NORTH MALUKU - Ahmad Yunan Arifin (Socio-Economics/Agribusiness Department, 2017)
Small islands have food development constraints due to their location characteristics which are dispersed and isolated. These small islands have limited capacity of land resource along with low efficiency of food distribution so that it influences sufficiency level of affordable food availability. Therefore, the aims of this research are: (1) to analyze regional food balance to fulfil food and nutrition needs; (2) to analyze the direction of food production development with small island basis; and (3) to analyze the interaction pattern of food distribution among small islands to ensure sufficiency food availability. This research was conducted in March-December 2016 in South Halmahera Regency. This research design is explorative using primary and secondary data. Primary data was collected by observation results, interview, and Focused Group Discussion (FGD). The result research shows that land optimization for the development of Wetland Food Crops (TPLB), Dry land Food Crops (TPLK), and Annual Food crops (TPT) are able to fulfil South Halmahera people’s food needs and its land availability surplus is 5.159,2; 34.834,9 and 21.971,0 ha. Interaction pattern among small island is needed for food availability from TPLK and TPLB in Bacan and Makian Small Island. Interaction pattern among small islands is needed for rice availability in all sub district of South Halmahera by optimize land resource potential, system recovery of land transportation and port warehouse in every small islands, empowerment of citizen ship in rice distribution from small island centre to every sub districts as well as TPLK and TPT distribution from nearby sub district in the same small island.